Reactivating the ARF-p53 axis in AML cells by targeting ULF - Chen, Delin (Landes Bioscience, 2010)
The tumor suppressor ARF plays an essential role in the cellular response to oncogenic stress mainly through activation of p53. Nucleophosmin (NPM), a multifunctional protein, forms a stable protein complex with ARF in the nucleolus and protects ARF from the proteasome-mediated degradation. Notably, NPM is mutated in about one third of acute myeloid leukaemia (AML) patients and these mutations lead to aberrant cytoplasmic dislocation of nucleophosmin (NPM-c). Cytoplasmic NPM mutants lose their abilities to retain ARF in the nucleolus and fail to stabilize ARF. Thus, activation of the ARF-p53 axis is significantly compromised in these AML cells. We have recently identified the ubiquitin ligase of ARF (ULF) as a key factor that controls ARF turnover in human cells. Here, we found that the steady levels of both ARF and p53 are very low in human acute myeloid leukaemia OCI-AML3 cells expressing cytoplamsic dislocated nucleophosmin (NPM-c). As expected, ARF is very unstable and rapidly degraded by proteasome. Nevertheless, ULF knockdown stabilizes ARF and reactivates p53 responses in these AML cells. These results further demonstrate that ULF is a bona fide E3 ligase for ARF and also suggest that ULF is an important target for activating the ARF-p53 axis in human AML cells.